Does long-distance air travel associated with the Sevens World Series increase players` risk of injury? - Fuller, C. W.; Taylor, A. E.; Raftery, M. (British Journal of Sports Medicine, 2015)
Objective: To assess whether players who cross =6 time zones and/or undertake =10 h air travel prior to competition experience a higher risk of injury during the Sevens World Series than players not required to undertake this level of travel.